Effectiveness of Conservation Measures in Reducing Runoff and Soil Loss Under Different Magnitude-Frequency Storms at Plot and Catchment Scales in the Semi-arid Agricultural Landscape. - Zhu, T. (Environmental Management, 2016)
In this study, multi-year stormflow data collected at both catchment and plot scales on an event basis were used to evaluate the efficiency of conservation. At the catchment scale, soil loss from YDG, an agricultural catchment with no conservation measures, was compared with that from CZG, an agricultural catchment with an implementation of a range of conservation measures. With an increase of storm recurrence intervals in the order of <1, 1-2, 2-5, 5-10, 10-20, and >20 years, the mean event sediment yield was 639, 1721, 5779, 15191, 19627, and 47924 t/km in YDG, and was 244, 767, 3077, 4679, 8388, and 15868 t/km in CZG, which represented a reduction effectiveness of 61.8, 55.4, 46.7, 69.2, 57.2, and 66.8 %, respectively. Storm events with recurrence intervals greater than 2 years contributed about two-thirds of the total runoff and sediment in both YDG and CZG catchments. At the plot scale, soil loss from one cultivated slopeland was compared with that from five conservation plots. The mean event soil loss was 1622 t/km on the cultivated slopeland, in comparison to 27.7 t/km on the woodland plot, 213 t/km on the grassland plot, 467 t/km on the alfalfa plot, 236 t/km on the terraceland plot, and 642 t/km on the earthbank plot. Soil loss per unit area from all the plots was significantly less than that from the catchments for storms of all categories of recurrence intervals.